The dimensions of accounting profession in the view of high school students as the generation z - Saarce Elsye Hatane; Kethrine Aprilia Willianto; Cindy Priscilia Junaidi; Claudia Jessica (Intelektual Pustaka Media Utama, 2019)
The purpose of this study is to analyze the perceptions of students from high school, who are the current generation Z, about the accounting profession. This study uses questionnaires that are shared online with data processing using factor analysis and one way ANOVA different tests. The comparison test was done between indicators of grade, major, school type, as well as variables, which include structure, precision, solitary, interest, and remaining variables. The interest in the accounting profession is found in social students (from high schools) and business administration students (from vocational schools). Other results also show that students in Private Vocational and Public High Schools have the most significant potential to be interested in the accounting profession. This research is limited to different test methods. Future studies can conduct a causal analysis of the factors that influence the choice of students in choosing the accounting profession. This research contributes to the investigation of students' perceptions of the accounting profession, which was conducted for the first time in Indonesia, especially in secondary schools in East Java.